Benefaction of Nutraceuticals for Human Health: Review - Mohammad Nadeem Khan; Ashok Kumar; Praveen Chand Dubey; Mohammad Rafi (Recent Trends in Infectious Diseases, 2023)
Nutraceuticals are a broad category of palatable natural chemicals that are thought to offer benefits beyond their nutritional content. These can include foods high in nutrients, foods with therapeutic properties, or certain ingredients found in some foods, like dietary fiber, hydrolyzed protein, garlic, ginger, omega-3, soybean, minerals, vitamins, fortified foods, enriched foods, and even recombinant goods. People are becoming more concerned about their health due to the long work hours and psychological strains of the modern lifestyle, which is causing a rise in life-threatening illnesses. Nutraceuticals are categorized according to their type and mechanism of action. The several kinds of nutraceuticals and their possible anti-cancer, antioxidant, anti-inflammatory, and anti-lipid qualities are examined in this review along with their potential therapeutic uses against cancer. The conversation covers various modes of action, uses, consumer safety concerns, as well as present and potential trends in the nutraceutical industry
Keywords: Anti-oxidant; Nutrient; Probiotics; food supplement; hypertension; life style; well-being